Physicochemical properties of functionalized carbon-based nanomaterials and their toxicity to fishes. (August 2016) - Felix, Lindsey C.; Ede, James D.; Snell, Dana A.; Oliveira, Taiane M.; Martinez-Rubi, Yadienka; Simard, Benoit; Luong, John H.T.; Goss, Greg G.
Abstract: Chemical functionalization to tailor surface properties of nanomaterials (NMs) is expected to broaden their scope of potential applications but may also be used to modify NM toxicity. We have examined the physicochemical properties of single-walled carbon nanotubes (SWCNTs) with varying degrees of carboxylic acid group functionalization, two types of lignin-wrapped SWCNTs, as well as nonfunctionalized SWCNTs. Zebrafish ( Danio rerio ) embryos were exposed to 1, 10, 50, 100 or 200 mg/L functionalized and nonfunctionalized SWCNTs for up to 72 h; measured endpoints included survival, hatching success, and alteration in gene expression. We have also characterized carboxylated cellulose nanocrystals (CNCs) and examined their effects both in vivo using zebrafish and in vitro using three channel catfish ( Ictalurus punctatus ) cell lines. While nonfunctionalized SWCNTs did not affect survival or hatch of embryos, carboxylic acid functionalized SWCNTs accelerated hatching and lignin-wrapped SWCNTs both decreased survival and delayed hatch at all time points tested. Carboxylated CNC exposure decreased the viability of 1G8 and 28S.3 catfish cells. We suggest that surface functionality affects SWCNT characteristics and plays a key role in determining their toxicity.